POSITIVE EFFECTS OF DIET CHANGE ON SHEDDING OF SALMONELLA SPP. IN THE FECES OF CAPTIVE FELIDS - Lewis, Charles E.; Bemis, David A.; Ramsay, Edward C. (Journal of zoo and wildlife medicine, 2002)
A high prevalence of fecal Salmonella shedding in a collection of healthy exotic felids precipitated a change to two new commercially available feline diets. One year after initiation of the new diets, 18 fecal samples from individual felines, their exhibits, and representative samples of the diets were cultured for Salmonella spp. Only one culture grew a Salmonella sp. Salmonella uganda was cultured from the feces of one snow leopard (Felis uncia). Feeding a diet with minimal to no Salmonella contamination lowered Salmonella shedding rates in this collection of captive exotic felids.